2023
DOI: 10.1038/s41368-023-00228-1
|View full text |Cite
|
Sign up to set email alerts
|

RANKL+ senescent cells under mechanical stress: a therapeutic target for orthodontic root resorption using senolytics

Abstract: In dentistry, orthodontic root resorption is a long-lasting issue with no effective treatment strategy, and its mechanisms, especially those related to senescent cells, remain largely unknown. Here, we used an orthodontic intrusion tooth movement model with an L-loop in rats to demonstrate that mechanical stress-induced senescent cells aggravate apical root resorption, which was prevented by administering senolytics (a dasatinib and quercetin cocktail). Our results indicated that cementoblasts and periodontal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 74 publications
(90 reference statements)
0
2
0
Order By: Relevance
“… 33 , 58 , 60 The intronic enhancer in osteocytic cells is activated by cellular senescence signals, 58 which were also shown to stimulate RANKL expression in periodontal ligament cells and cementoblasts. 61 We previously demonstrated that periodontitis-induced bone loss and osteoclast development were markedly suppressed when RANKL was deleted in osteoblastic cells and periodontal ligament cells. 4 In our scRNA-seq dataset, the osteoblastic cells (characterized by expression of Sp7 and Runx2 ) and periodontal ligament fibroblasts (characterized by expression S100a4 and Postn ) were clustered as a single population due to the limited number of cells compared to previous scRNA-seq studies.…”
Section: Discussionmentioning
confidence: 99%
“… 33 , 58 , 60 The intronic enhancer in osteocytic cells is activated by cellular senescence signals, 58 which were also shown to stimulate RANKL expression in periodontal ligament cells and cementoblasts. 61 We previously demonstrated that periodontitis-induced bone loss and osteoclast development were markedly suppressed when RANKL was deleted in osteoblastic cells and periodontal ligament cells. 4 In our scRNA-seq dataset, the osteoblastic cells (characterized by expression of Sp7 and Runx2 ) and periodontal ligament fibroblasts (characterized by expression S100a4 and Postn ) were clustered as a single population due to the limited number of cells compared to previous scRNA-seq studies.…”
Section: Discussionmentioning
confidence: 99%
“…They observed that cultured human diploid fibroblasts exhibited a finite number of divisions (40–60 population doublings), a phenomenon attributed to intrinsic factors, which were later identified as telomere shortening. Different external and internal stress and developmental signals trigger cellular senescence in response to cellular damage, including telomere shortening, DNA damage, oncogenic activation, radiation, oxidative and genotoxic stress, epigenetic changes, perturbed proteostasis, mitochondrial dysfunction, inflammation, nutrient deprivation and mechanical stress ( Kuilman et al, 2010 ; Muñoz-Espín et al, 2013 ; Storer et al, 2013 ; Hernandez-Segura et al, 2018 ; Kumari and Jat, 2021 ; Huang et al, 2022 ; Zhou et al, 2023 ).…”
Section: Introduction To Cellular Senescencementioning
confidence: 99%